Clinicopathological Impact of ABCC1/MRP1 and ABCC4/MRP4 in Epithelial Ovarian Carcinoma. (19th August 2013) - Bagnoli, Marina; Beretta, Giovanni L.; Gatti, Laura; Pilotti, Silvana; Alberti, Paola; Tarantino, Eva; Barbareschi, Mattia; Canevari, Silvana; Mezzanzanica, Delia; Perego, Paola
Abstract : Ovarian cancer is the main cause of death from gynaecological malignancies. In spite of the efficacy of platinum-paclitaxel treatment in patients with primary epithelial ovarian carcinoma, platinum-based chemotherapy is not curative and resistance remains one of the most important causes of treatment failure. Although ABC transporters have been implicated in cellular resistance to multiple drugs, the clinical relevance of these efflux pumps is still poorly understood. Thus, we examined the prognostic role of transporters of the MRP family (i.e., ABCC1/MRP1, ABCC4/MRP4) to gain insights into their clinical impacts. A case material of 127 patients with ovarian carcinoma at different stages and histotypes was used. The expression of MRP1 and MRP4 was examined by immunohistochemistry using tissue microarrays in tumor specimens collected at the time of initial surgery expression. We found an association between MRP1 expression and grading, and we observed that MRP4 displayed an unfavourable impact on disease relapse in multivariate analysis (HR = 2.05, 95% CI: 1.01–4.11; P = 0.045 ). These results suggest that in epithelial ovarian cancer, MRP1 may be a marker for aggressiveness because its expression was associated with tumor grade and support that MRP4 may play an unfavourable role in disease outcome.